Physics with Fundamentals of Biophysics - Posudin, Yuriy (Printline, 2014)
The text-book “Physics with Fundamentals of Biophysics” published in English is intended for the students who attend the English-speaking lectures in educational institutions of Ukraine; it can be useful for the foreign students and post-graduate students, translators and everybody who is interested in English terminology in the field of physics and biophysics. The main objectives of the course “Physics with Fundamentals of Biophysics” is to expose principal laws and theses of physics which make it possible to study general regularities of natural phenomena; to apply the principles and methods of the physical sciences to biological problems; to consider the biophysical problems which are concerned with the viability of living objects (plants, animals, microorganisms) and their interaction with the environment; to elucidate possible application of physical instrumentation to agricultural, biological, ecological, and medical practice. The text-book is supplied with the examples of solutions of practical biophysical problems, control questions pertaining to those problems that require clarification. Rating system of estimation of students´ level of knowledge is offered also. Each text modulus contains the vocabulary of physical and biophysical terms. The informative material is given in appendix

Підручник “Physics with Fundamentals of Biophysics” (“Фізика з основами біофізики”), виданий англійською мовою, призначений саме для підготовки студентів, що слухають лекції англійською мовою в навчальних закладах ІІІ-IV рівнів акредитації України; він може бути корисним для іноземних студентів та аспірантів, перекладачів та всіх, хто цікавиться англомовною термінологією в галузі фізики та біофізики Основна мета підручника - навести основні положення, закони та теорії з курсу загальної фізики; розглянути фізичні процеси та механізми, що складають основу життєдіяльності живих організмів – рослин, тварин, мікроорганізмів; викласти проблеми впливу зовнішніх фізичних факторів на живі організми та їх здатності реагувати на ці фактори; висвітлити принципи дії та можливі застосування сучасних фізичних методів та приладів у сільськогосподарській, біологічній, екологічній та медичній практиці. Підручник містить приклади розв’язання практичних біофізичних проблем, контрольні завдання для перевірки засвоєння матеріалу студентами та запитання, відповіді на які студенти зможуть дати у разі ознайомлення із відповідними розділами підручника. Для оцінки знань студентів пропонується рейтингова система. Кожний змістовний модуль має словник фізичних та біофізичних термінів. Інформативний матеріал представлений у додатку.
Фізика з основами біофізики
Keywords: Physics; фізика; біофізика; Fundamentals of Biophysics